PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBASIS KOMPUTER POKOK BAHASAN LINGKARAN UNTUK KELAS VIII SEKOLAH MENENGAH PERTAMA - Malalina; Kesumawati, Nila (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2014)
This development research was conducted in order to (1) develop valid and practical computer-based interactive learning materials on circles and (2) identify their effect on the leraning outcomes after they learned the materials at SMP Nurul Iman Palembang. The subjects of this research were the 34 students class VII. 7 of this school. The data were collected from walk through, documentation, observation and language. The average results were 87,11%. The materials were practical as shown by one to one try outs. The stedents achieved an average score of 73,33 that feel in the good range, and were involved the learning activities the very active (66,7%) and active (33,3%) ranges. In small group work, the students achieved an average score of 73,33 (good category) and showed levels of very active (50%). The rest were active (16,67%), fairly active (16,67%) and less active (16,67%) resepectively. Based on field test results, the materials gave effect on the students’ potential and learning outcomes. The final results of the students’ achievement were as follow : very good (20,59%), good (58,8%), adn fair (20,59%). In term of their activity levels, they were grouped into very active (27,45%), active (45,10%) and fairly active (27,45%). DOI: https://doi.org/10.22342/jpm.8.1.1861.55-70